PENGEMBANGAN E-MODUL RESEARCH BASED LEARNING MENGGUNAKAN LECTORA INSPIRE APPLICATION PADA PEMBELAJARAN IPAS UNTUK MENDUKUNG MENDEKA BELAJAR SISWA SEKOLAH DASAR - Sonia Yulia Friska; Estuhono; Riska Kurnia Fitri (STKIP Subang, 2023)
The research is that students have difficulty understanding the subject matter because of the new curriculum and during the learning process the teacher only uses books as a learning resource so that student learning motivation in science learning does not look good because there are no teaching materials other than books so students feel bored because learning is not interesting and fun. The purpose of this study is to find out how the accuracy of the content, the implementation of the use and how the understanding of science learning after using the E-module. This research is research and development (R&D). The model used, namely the plopm model, this study consists of three stages. The research phase. Introduction (Preliminary research), the prototype stage (development or prototyping) and the assessment phase (assessment phase). The results of the validation assessment by the three validators obtained an average score of 89.9% with a very valid category. the results of the practicality assessment of the e-module conducted by teachers and fourth grade elementary school students obtained an average score of 90.7% in the very practical category. The effectiveness results carried out by all fourth grade elementary school students obtained a percentage of 80% in the effective category. So, the conclusion of this study is that the development of e-modules based on research based learning using the Lectora Inspire Application has valid, practical and effective criteria.